Advocating neuroimaging studies of transmitter release in human physical exercise challenges studies - Henning Boecker; Ahmed Othman; Sarah Mueckter; et al (Dove Medical Press, 2010)
Henning Boecker1, Ahmed Othman1, Sarah Mueckter1, Lukas Scheef1, Max Pensel1, Marcel Daamen1, Jakob Jankowski1, HH Schild2, TR Tölle3, M Schreckenberger41FE Klinische Funktionelle Neurobildgebung, Radiologische Universitätsklinik, Friedrich-Wilhelms–Universität Bonn, Germany; 2Radiologische Universitätsklinik, Friedrich-Wilhelms-Universität Bonn, Germany; 3TUM Neurologische Klinik und Poliklinik im Neuro-Kopf-Zentrum, Klinikum rechts der Isar der Technischen Universität München, München, Germany; 4Klinik und Poliklinik für Nuklearmedizin am Mainzer Universitätsklinikum, Johannes Gutenberg-Universität, Mainz, GermanyAbstract: This perspective attempts to outline the emerging role of positron emission tomography (PET) ligand activation studies in human exercise research. By focusing on the endorphinergic system and its acclaimed role for exercise-induced antinociception and mood enhancement, we like to emphasize the unique potential of ligand PET applied to human athletes for uncovering the neurochemistry of exercise-induced psychophysiological phenomena. Compared with conventional approaches, in particular quantification of plasma beta-endorphin levels under exercise challenges, which are reviewed in this article, studying opioidergic effects directly in the central nervous system (CNS) with PET and relating opioidergic binding changes to neuropsychological assessments, provides a more refined and promising experimental strategy. Although a vast literature dating back to the 1980s of the last century has been able to reproducibly demonstrate peripheral increases of beta-endorphin levels after various exercise challenges, so far, these studies have failed to establish robust links between peripheral beta-endorphin levels and centrally mediated behavioral effects, ie, modulation of mood and/or pain perception. As the quantitative relation between endorphins in the peripheral blood and the CNS remains unknown, the question arises, to what extent conventional blood-based methods can inform researchers about central neurotransmitter effects. As previous studies using receptor blocking approaches have also revealed equivocal results regarding exercise effects on pain and mood processing, it is expected that PET and other functional neuroimaging applications in athletes may in future help uncover some of the hitherto unknown links between neurotransmission and psychophysiological effects related to physical exercise.Keywords: positron emission tomography, beta-endorphins, opioids